Safety data sheets for chemical laboratories associated with environmental engineering - Ibragimov Irek (E3S Web of Conferences, 2024)
Safety data sheets for chemical laboratories associated with environmental engineering are an essential document for conducting various experiments in laboratories. This document contains a list of toxic substances, a first aid kit, instructions for the proper disposal of waste, and other things that will definitely increase safety in the proper operation of laboratories. Such a passport has a reference character. Its purpose is to provide consumers, production and enterprise personnel, emergency services personnel with sufficient information about the safe handling of specific products and about the actions to be taken in case of danger to protect people and the environment. The structure of the passport and its contents are precisely defined by international rules. A chemical laboratory is a room specially adapted for technical and research experiments.